Double space : rethinking Singapore's public spaces - Tan, Hillary Jia Lerk (2018)
Double Space is an illustrated feature documenting some of the creative informal activities taking place in our neighbourhoods — in void decks, parks, multi-storey carparks and forested areas we ignore on our way to work and school. These activities range from subversive street art to benign free ‘markets’, but they all have one thing in common: they re-envision what can be done in our public spaces.